2005
DOI: 10.1089/neu.2005.22.719
|View full text |Cite
|
Sign up to set email alerts
|

Synaptogenesis in the Hippocampal CA1 Field following Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) results in both acute and chronic disruption of cognitive ability that may be mediated through a disruption of hippocampal circuitry. Experimental models of TBI have demonstrated that cortical contusion injuries can result in the loss of specific neurons in the CA3 subfield of the ipsilateral hippocampus, resulting in partial loss of afferents to the CA1 subfield. Numerous studies have documented the ability of the central nervous system to compensate for deafferentation by initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
127
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 78 publications
11
127
0
1
Order By: Relevance
“…Altered energy metabolism and oxidative stress negatively affects synaptic plasticity and cognitive function though oxidation of synaptic proteins [18,20]. Oxidative stress contributes to synaptic dysfunction and disconnection, with impaired mitochondrial transport to the synapses contributing to both neuronal death and neuritic degenerative cascades [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered energy metabolism and oxidative stress negatively affects synaptic plasticity and cognitive function though oxidation of synaptic proteins [18,20]. Oxidative stress contributes to synaptic dysfunction and disconnection, with impaired mitochondrial transport to the synapses contributing to both neuronal death and neuritic degenerative cascades [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of oxidative stress both the function and transport of mitochondrial to synaptic regions is impaired, decrease synaptic function [15,16], which results in neurodegeneration after brain injury [17,18]. A recent study reported that oxidative stress alters the function of PSD-95 by decreasing a voltage-gated potassium channel that is closely linked to the PSD [19], suggesting that synapse loss and replacement, known to occur following TBI [20], could be modulated by the levels of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Acute perturbations of glial function and ionic fluxes highlight the transient nature of injury-induced alterations that can alter excitability [21,45]. Lastly, disruption of synapse function or number [77,80], without neuronal loss, could contribute to the acute injury-induced deficits in conditioned fear, prompting future studies at the ultrastructural level. It follows, therefore, that the natural course of functional recovery in experimental and clinical TBI may be amenable to therapeutic intervention to overcome the transient lesion.…”
Section: Discussionmentioning
confidence: 99%
“…1 Multiple primary and secondary injury cascades are involved in TBI, which result in delayed neuronal dysfunction, synapse loss, and cell death. [2][3][4][5][6][7][8][9] These secondary injury cascades can occur very rapidly, within minutes or hours after the trauma and last for days or weeks. Although there are many different factors, most researchers believe that pharmacologic intervention following trauma can disrupt these cascades and result in a more positive outcome.…”
mentioning
confidence: 99%